Osea Felici: an italian reporter in Brazil of the twenties - Mauro, Sergio [UNESP]; Campos Mauro, Claudia Fernanda de [UNESP] (Univ Estadual Paulista-unesp, 2015)
Starting with a few observations about the first italian writes who describe Brazil, this essay intends to remark the Oseas Felicis' book. Felici wrote the book II Brasile come in 1923. He was a italian reporter who visited Rio de Janeiro in 1922-1923. We want to underline in this essay the author's remarks about the brazilian culture and economy, the literary stile of the italian reporter and the his prejudices which have ideologic nature.
Keywords: Italian jornalismo; Literary style; Italian view about Brazil